Analisis Penerapan Sistem Informasi Akuntansi Dalam Menunjang Efektivitas Pengendalian Internal Pemberian Kredit Pada Bank Pembangunan Daerah Jawa Barat Dan Banten, Tbk KCP Jampang Kulon - Susilawati, Pina; Nurodin, Idang (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This study aims to find out 1) know the application of accounting information systems, 2) know the application of accounting information systems for lending 3) know the application of effective internal control systems at PT. Regional Development Bank of West Java and Banten, Tbk KCP Jampang Kulon. The type of research used is a descriptive qualitative method, where this research data is obtained from direct observation and interviews with Bank BJB and obtained from documents related to this study. The results of this study show that the accounting information system at Bank BJB KCP Jampang Kulon has been implemented and most of them are good enough according to the provisions at Bank BJB and have fulfilled the elements of the accounting information system components. However, there are weaknesses in the system used, namely there are still problems that occur such as errors and also the sharing of accounts with other users so that it can result in errors in transactions and the blame party is the owner of the account. As for the accounting information system for lending, it has also been implemented in accordance with the lending procedure at Bank BJB KCP Jampang. In addition, the internal control system of Bank BJB KCP Jampang Kulon has also been implemented and most of them are effective and have fulfilled the internal control components according to COSO. In practice, the components that are run are effective, but the LMS system used is still not effective because there are still errors and there are still sharing SLIK accounts with other KCPs so that it can hamper the SLIK submission process.